Impact of Sustainable Product Quality on BUMDes Performance: The Mediating Role of Community Satisfaction - Mashuri; Dewi Oktayani; Erlindawati (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in promoting sustainable local economic development. Sustainable product quality is a key factor in enhancing competitiveness and community acceptance. However, BUMDes performance is not solely determined by product quality, but also by the level of community satisfaction as users. Therefore, it is important to examine the relationship between sustainable product quality and BUMDes performance by considering the mediating role of community satisfaction. Purpose - This study aims to analyze the effect of sustainable product quality on BUMDes performance, with community satisfaction as a mediating variable. This research is important to understand how the implementation of sustainable product quality can enhance the performance of Village-Owned Enterprises (BUMDes) through increased community satisfaction as users of BUMDes products or services. Method - This study employs a quantitative approach with respondents consisting of community members who use BUMDes products or services. The sampling technique used is purposive sampling. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to examine the relationships among variables as well as the mediating role of community satisfaction. Findings - The results indicate that sustainable product quality has a positive and significant effect on community satisfaction (β = 0.696; p < 0.001). Furthermore, community satisfaction has a positive and significant effect on BUMDes performance (β = 0.584; p < 0.001). In addition, sustainable product quality also has a direct effect on BUMDes performance (β = 0.297; p < 0.001). Mediation testing results show that community satisfaction significantly mediates the relationship between sustainable product quality and BUMDes performance (β = 0.406; p < 0.001). The structural model demonstrates a satisfactory explanatory power, with an R² value of 0.670 for BUMDes performance and 0.484 for community satisfaction. Implications – The findings of this study suggest that improving sustainable product quality can enhance community satisfaction and ultimately strengthen BUMDes performance in supporting sustainable rural economic development.